Pengaruh Konsentrasi Inokulum pada Fermentasi Nira Aren (Arenga Pinnata) Secara Aerob Terhadap Konversi Asam Asetat - Karim Abdullah; Chairul Chairul; Syelvia Putri Utami (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Acetic acid is an organic chemical compound that gives a sour taste to vinegar and a sharp odor. Acetic acid is obtained from bioethanol using Arenga plant. Microorganism that used for processing the arenga plant into bioetanol was Saccharomyces cerevisiae and microorganism that used for processing bioethanol into acetic acid was Acetobacter aceti. The purpose of this study is to determine the effect of Acetobacter aceti inoculum concentration and fermentation time on acetic acid conversion rates. The research phase consisted of raw material preparation and making of inoculum, fermentation and analysis. The concentration of inoculum used in this study varied at 10%; 15%; and 20%. The fermentation results are taken after 3, 6, 9 and 12 days. Optimal bioethanol fermentation yield 3% (v / v) or 23.67 g / L, sugar conversion 73.17% at 10% inoculum concentration and produce the highest acetic acid 2.56% or 25,54 g / L at 12 days fermentation at concentration 10% inoculum.Keywords: Acetic acid, bioethanol, arenga plant, fermentation, conversion.